Autoimmune Liver Diseases: The Value of Geographic Differences - Beenet, Linda (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Beenet L. Autoimmune liver diseases: The value of geographic differences. Turk J Gastroenterol. 2022;33(3):271.